Heated tobacco products use in Chinese adults in Hong Kong: a population-based cross-sectional study. Issue 3 (20th April 2019) - Wu, Yongda Socrates; Wang, Man Ping; Ho, Sai Yin; LI, Ho Cheung William; Cheung, Yee Tak Derek; Tabuchi, Takahiro; Kwong, Antonio CS; Lai, Vienna; Lam, Tai Hing
Abstract : Introduction: We investigated heated tobacco products (HTPs) use and associated factors in Chinese adults in Hong Kong where HTPs are not formally marketed yet, and cigarette smoking prevalence was the lowest in the developed world. Methods: A population-based landline telephone survey in 2017 interviewed 5131 (45.2% male; 26.7% aged ≥60) adults to collect information on awareness, intention to use, ever use of HTPs, cigarette smoking status and sociodemographic characteristics. Descriptive statistics were weighted by the age, sex and smoking status of the Hong Kong adult population. Sociodemographics were mutually adjusted in logistic regression to yield adjusted ORs (AORs) for awareness of HTPs, controlling for smoking status. Results: Overall, 11.3% (95% CI 10.0% to 12.7%) were aware of HTPs and 1.0 % (0.8%–1.2%) had ever used it. Awareness was associated with aged 40–49 years (AOR 1.37, 95% CI 1.01 to 1.87) or 30–39 years (2.03, 1.41–2.91) (vs ≥60 years), born in Hong Kong (1.37, 1.11–1.68) and higher monthly household income (p for trend 0.001). Ever HTP users had higher educational attainment and monthly household income, and more were aged 30–39 and economically active (all p<0.003). In never HTP users, intention to use HTPs (7.3%, 4.9%–10.8%) were more prevalent in respondents with similar characteristics (all p<0.008). More current (vs never) smokers were aware of HTPs, intent to use HTPs and had ever used HTPs (all p<0.001). Conclusion: Higher socioeconomic status was associated with HTP use and intention to use. Public health education on HTPs is needed especially for this high-risk group.